Komparasi Kebijakan Australia terhadap Indonesia Masa Partai Buruh dan Liberal - Thufail, Afif (Journal of Integrative International Relations, 2020)
Australia and Indonesia are neighboring countries which have different historical, ethnic and community factors that cause frequent upheavals. Even so, Australia and Indonesia, like other neighboring countries, often have good relations that benefit each country. Australia has two parties that are very dominant in the political contestation; The Liberal Party and the Labor Party. This article discusses the question of whether there were sufficient differences when the government in Australia was led by the Liberal Party and the Labor Party which influenced the foreign policy taken by the Australian Government towards Indonesia.